Language-in-education policy in low-income, postcolonial contexts: towards a social justice approach. Issue 3 (2nd July 2016) - Tikly, Leon
ABSTRACT: The article considers how language-in-education policy in low-income, postcolonial countries may be better understood from a social justice perspective and some of the implications for policy, practice and research that arise from this. The article starts with a critical overview of the two dominant approaches towards conceptualising language-in-education policy, namely the instrumental and rights-based approaches. The article then sets out a social justice approach that builds critically on a rights-based perspective. Key features of the approach include considering language-in-education as a capability that has the potential to contribute to human well-being and to social justice and understanding the pedagogical, institutional and wider social barriers to achieving linguistic social justice in education and means for overcoming these barriers. Based on this understanding the article then sets out a research agenda that can assist in realising linguistic social justice in education across the three inter-related domains of the school, the home/community and the education system.